Surveillance of Adverse Events Following Vaccination against SARS-CoV-2: Guillain–Barré Case Study, Hail, Saudi Arabia - Farhan Alshammari (Hail Journal of Health Sciences)
Guillain-Barré syndrome (GBS) is the leading cause of acute flaccid paralysis in developed countries, characterized by weakness, sensory abnormalities, and autonomic dysfunction. Despite its prevalence, the etiology and pathophysiology of GBS remain unclear. However, recent studies have suggested a possible association between GBS and vaccination, including those for meningococcal, polio, influenza, rabies, and SARS-CoV-2 (coronavirus disease 2019 [COVID-19]). In fact, the first case of GBS following the Pfizer-BioNTech COVID-19 vaccine was recently reported in a teenage boy with no recent history of viral or bacterial illnesses, he presented by progressive bilateral lower limb weakness ascending to involving the upper limbs within 1 day. He had no history of any chronic illness, and no history of recent SARS-COV-2 infection. This unexpected adverse reaction highlights the need for further research on the occurrence of GBS in connection with vaccination, particularly in the Middle East, where data are limited. Vaccine-induced GBS can often be misdiagnosed or undiagnosed, making it important for health-care professionals to understand its symptoms and potential causes. To better understand how to diagnose and treat GBS occurrence in the context of COVID-19 vaccination, further research is urgently needed.